Research on fall protection devices based on adaptive structured fabrics - Jiang, Chenglin (Nanyang Technological University, 2022)
As the most common accident, falls not only cause serious injury to the body, but also impose a huge financial burden on the family. And the probability of falling increases with the irreversible process of population aging. Hence, many solutions are developed to prevent fall or mitigate the fall injury. Basically these methods can be divided into four categories, namely prevention, intervention, mitigation and recovery. Here, a fall protection device based on intervention idea is proposed for preventing fall by providing in time assistive force at the onset of instability in this dissertation. The proposed fall device mainly consists of three parts, structured fabric base-suit, fall detection and trigger device and negative pressure auxiliary device. First, the tunable mechanical properties structured fabric and harnesses frame are used to fabricate the soft base-suit. Then, the threshold fall detection and trigger devices are implemented by a microcontroller board and IMU modules. Finally, a portable negative pressure device is designed for rapid activation of base-suit. Moreover, the simulation experiment results of integrated prototype verify the feasibility and rationality of the design. Although the prototype has achieved the anticipation such as assistive force and portability, the proposed fall protection device is currently only in the initial stage. The results of this dissertation have shown a promising potential of proposed fall protection device.